2020
DOI: 10.3390/jcm9020367
|View full text |Cite
|
Sign up to set email alerts
|

Using Whole Breast Ultrasound Tomography to Improve Breast Cancer Risk Assessment: A Novel Risk Factor Based on the Quantitative Tissue Property of Sound Speed

Abstract: Mammographic percent density (MPD) is an independent risk factor for developing breast cancer, but its inclusion in clinical risk models provides only modest improvements in individualized risk prediction, and MPD is not typically assessed in younger women because of ionizing radiation concerns. Previous studies have shown that tissue sound speed, derived from whole breast ultrasound tomography (UST), a non-ionizing modality, is a potential surrogate marker of breast density, but prior to this study, sound spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Our study demonstrated the independence of stiffness from sound speed and adds new information to the interpretation of the whole breast and tissue properties of common masses. Previous work has shown strong correlations between the higher values of whole-breast average UST sound speed and mammographic density, which are representative of the underlying fibroglandular tissue [ 6 , 10 , 12 ]. In this study we have shown that higher sound speed fibroglandular tissue can be further characterized by its relative stiffness properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study demonstrated the independence of stiffness from sound speed and adds new information to the interpretation of the whole breast and tissue properties of common masses. Previous work has shown strong correlations between the higher values of whole-breast average UST sound speed and mammographic density, which are representative of the underlying fibroglandular tissue [ 6 , 10 , 12 ]. In this study we have shown that higher sound speed fibroglandular tissue can be further characterized by its relative stiffness properties.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies of SoftVue stiffness imaging may better characterize cancer subtypes and benign findings. While it is encouraging that UST shows promise in ongoing studies of risk evaluation [ 12 ], chemoprevention monitoring [ 17 ] and imaging responses to neoadjuvant chemotherapy [ 13 ], further studies are needed to assess the role of UST stiffness imaging in routine clinical practice. Development of computer-aided diagnostics will automate the labor-intensive, hand-tracing of tumor margins used as a baseline in this study, which will extend to multiple slices for improved volumetric accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature changes for many treatments can be measured for avoiding harm in medical sectors. The improving electrocardiogram (ECG) is associated with the measured internal conductivity distributions [11]. Impedance distributions are structured with the properties of the objects based on several bioelectrical properties of the tissues in medical applications.…”
Section: Figure 1 Block Diagram Of Eit System Work Flowmentioning
confidence: 99%